On dichotomic maps for non autonomous discrete equations - Marconato, Suzinei A.S. [UNESP] (My University, 1997)
A new procedure is given for the study of stability and asymptotic stability of the null solution of the non autonomous discrete equations by the method of dichotomic maps, which it includes Liapunov's Method as a special case. Ex amples are given to illustrate the application of the method.